Assessing the Moderating Role of Job Burnout on the Relationship between Quality of Working Life and Job Performance among Nursing Staff of Teaching Hospitals Affiliated to Qazvin University of Medical Sciences - Sima Rafiei; Mohammad Zakaria Kiaiei; pejman sadeghi; Vahid Makhtoomi; Donya Asghari (Tehran University of Medical Sciences, 2019)
Background: One of the main important factors which affects nurseschr('39') job performance and potentially influences their capability in accomplishing their tasks and responsibilities is job burnout (JB). This study aimed to investigate the moderating role of JB on the relationship between QWL and job performance among nurseschr('39') employees in emergency departments of five training hospitals affiliated to Qazvin University of Medical Sciences in 2017.   Materials and Methods: This descriptive, cross-sectional study was conducted among 178 nurseschr('39') employees in emergency departments of five teaching hospitals affiliated to Qazvin University of Medical Sciences in 2017. In order to assess main variables of present study, three standard questionnaires consisted of Walton QWL, Maslach and Jackson job burnout and Paterson job performance were used. Descriptive statistics, Pearson correlation coefficient and moderated multiple regression analysis were used to analyze data. The level of significance was set less than 0.05.   Results: Study results revealed that most of the nursing staff had a low level of QWL, experienced a considerable JB with a moderate to high level of performance. Furthermore, QWL predicted 21% of variances regarding to job performance (R2=0.21, p=0.04). The moderated multiple regression results supported the hypothesis that JB had a significant effect on the relationship between QWL and nurseschr('39') job performance (β≠0, p=0.02).   Conclusion: Considering the importance of QWL and efforts to develop an appropriate condition to promote different aspects of QWL would play an important role in nurseschr('39') productivity and accomplishment of their performance goals.